Correlation between chronological age and third molar developmental stages in an Iranian population (Demirjian method) - Aria Khosronejad; Manijeh Navabi; Shirin Sakhdari; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2017)
Background: Third molar development is the only available tool for estimating the age of individuals after puberty. Since this tooth has very high interethnic variability, formulas calculated to estimate the age from its development stages cannot be generalized to other populations and should be adjusted for each region. Therefore, this study was conducted to evaluate this method in a sample of Tehran individuals for the first time, and also to compare the development of third molars across sexes and arches, and to estimate cutoff developmental stages for legal minor/major identification. Materials and Methods: A total of 150 dental patients aged between 15 and 25 years old were prospectively enrolled, and their Demirjian stages were recorded. The associations between chronological age and Demirjian stages were evaluated. Dental formation was compared between sexes and jaws. Cutoff stages were determined to identify legal minor/major cases (above or below 18 years old). Age estimation formula was found for this population. Results: Of the 150 included patients, 56 were males. The difference between the ages of males and females at each given developmental stage was nonsignificant (P > 0.05), except for the H stage. Age difference between same stage teeth of the maxilla and mandible was nonsignificant. Each of the G and H stages was significantly above 18 years old (P < 0.001). Furthermore, E and F stages were below 18 years old (P < 0.001). All the correlations between Demirjian stages and age were above 90% (all P< 0.001). Third molar development was positively affected by the chronological age (P = 0.000) and being maxillary (P = 0.000) but not sex (P = 0.113). Regression formula for age estimation was: age = 6.52+ (0.64 × sex) + (0.32 × arch) + (1.86 × Demirjian stage). Conclusion: Development of third molar might complete after the age 22. Iranian individuals with third molars at the G and H stages are likely above 18 while those at E and F are likely below 18. Pace of molar development differs for jaws, but intergender differences are open to further investigations.